IMPLEMENTASI ASAS-ASAS UMUM HUKUM KEBENDAAN DALAM UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Vivi Lia Falini Tanjung (Universitas Muhammadiyah Sumatera Utara, 2017)
The fiduciary guarantee agency is very helpful for the smoothness of business managed by the debtor, because the goods used as security for the repayment of its debts remains in its power. Fiduciary guarantee is a part of the material law, so the principles of material law must be adopted in the legal rules of the fiduciary guarantee agency, which is currently regulated in Act No. 42/1999, but this law needs to be revised, especially in relation to the registration of fiduciary collateral, fiduciary execution and the possibility of whether or not fiduciary assets should be used as a fiduciary guarantee again.